IMPLEMENTASI KURIKULUM MERDEKA PROGRAM MAGANG BERSERTIFIKAT DI ERA DIGITAL PADA DEPARTEMEN TATA RIAS DAN KECANTIKAN FAKULTAS PARIWISATA DAN PERHOTELAN UNIVERSITAS NEGERI PADANG - Murni, Astuti (AI Society & STMIK Indonesia, 2024)
The Independent Learning Curriculum is a curriculum that is here to answer the challenges of education in this digital era. Highly educated people are needed to face rapid technological changes in this digital era. In order to prepare highly educated people, universities as educational institutions need to take steps to collaborate with the industrial world in implementing the independent learning curriculum. This research aims to provide an explanation of the collaboration between universities, especially the Department of Cosmetology and Beauty and the beauty industry in implementing the independent learning curriculum. The results of this research are that collaboration between universities and industry can be carried out in the form of joint curriculum preparation, internships and joint research. The benefit of research for society is that it provides insight into the importance of collaboration between universities and industry in order to prepare superior people who are ready for developments in the digital era.